Crystallographic analysis of the binding modes of thiazoloisoindolinone non-nucleoside inhibitors to HIV-1 reverse transcriptase and comparison with modeling studies. - Ren, J; Esnouf, R; Hopkins, A; Stuart, D; Stammers, D (1999)
We have determined the crystal structures of thiazoloisoindolinone non-nucleoside inhibitors in complex with HIV-1 reverse transcriptase to high-resolution limits of 2.7 A (BM +21.1326) and 2. 52 A (BM +50.0934). We find that the binding modes of this series of inhibitors closely resemble that of "two-ring" non-nucleoside reverse transcriptase inhibitors. The structures allow rationalization of stereochemical requirements, structure-activity data, and drug resistance data. Comparisons with our previous structures suggest modifications to the inhibitors that might improve resilience to drug-resistant mutant forms of reverse transcriptase. Comparison with earlier modeling studies reveals that the predicted overlap of thiazoloisoindolinones with TIBO was largely correct, while that with nevirapine was significantly different.